The Influence of Profıtabılıty and Debt Ratıo Toward the Value of Stock Medıated by the Issuer’s Actıon (Empirical Study on Fishery Companies listed on the Indonesia Stock Exchange period 2008 – 2014) - Sitorus, Tigor (APMBA (Asia Pacific Management and Business Application), 2016)
This study aims to extend a model empirical research from the direct effect of the influencing of profitability and the debt ratio toward the Value of stock  to be a new model empirical research of  the mediating effect of Issuer’s action upon the influencing of profitability and debt ratio toward Value of stock. This research was conducted at the  Fishery Company listed in Indonesia Stock exchange period from  2008 to 2014. Structural Equation Model (SEM) by AMOS software 22.00 was used to analyze the data, and the result shows high goodness of fit while the simultaneous and individual tests generate significant result. The result of analysis shows that: (1) the Profitability gives significantly positive influence to Issuer’s Action, (2); the Profitability gives significantly positive influence toValue of stock , (3) the Debt Ratio gives significantly negative influence to Issuer’s Action,  (4); the Debt Ratio gives significantly negative influence to  Value of stock , (5); the Issuer’s Action gives significantly  positive influence to Value of stock , therefore the mediated effect of Issuer’s Action has more strength compared to direct effect of the Profitability and the Debt Ratio toward the Value of stock, so we may conclude that the result evidently shows the Issuer’s Action was able to mediate the influence of profitability and debt ratio toward Value of stock.